2022
DOI: 10.1186/s12913-022-07818-5
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a menstrual health intervention in a community-based sexual and reproductive health service for young people in Zimbabwe: a qualitative acceptability study

Abstract: Background Despite being fundamental to the health and well-being of women, menstrual health is often overlooked as a health priority and access to menstrual health education, products, and support is limited. Consequently, many young women are unprepared for menarche and face challenges in accessing menstrual health products and support and in managing menstruation in a healthy and dignified way. In this paper, we examine the acceptability of a comprehensive menstrual health and hygiene (MHH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
5
15
2
Order By: Relevance
“…Concerning the healthcare service providers, the SRH intervention was welcomed as it was perceived as "a hook" to attract adolescents, both in and out of school, and expose them to quality SRH information and services using varied formats. Our study's acceptance of the intervention corroborates earlier studies on the acceptability of SRH products in Zimbabwe [17] and Malawi [22], where similar acceptance was reported. Given the acceptability of the strategies, SRH interventions should be designed to be context-specific, adaptable to the users' needs and preferences, and SRH education prioritised for informed sexual choice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning the healthcare service providers, the SRH intervention was welcomed as it was perceived as "a hook" to attract adolescents, both in and out of school, and expose them to quality SRH information and services using varied formats. Our study's acceptance of the intervention corroborates earlier studies on the acceptability of SRH products in Zimbabwe [17] and Malawi [22], where similar acceptance was reported. Given the acceptability of the strategies, SRH interventions should be designed to be context-specific, adaptable to the users' needs and preferences, and SRH education prioritised for informed sexual choice.…”
Section: Discussionsupporting
confidence: 90%
“…The intervention was accepted in the community because it helped address the conflicts between personal beliefs and societal norms and expectations. This is in contrast to a study in Zimbabwe [17], where despite implementing PLOS ONE a community-based SRH intervention for healthcare providers and product sensitization, there were still challenges to overcoming the sociocultural barriers to SRH product acceptability. Concerning the healthcare service providers, the SRH intervention was welcomed as it was perceived as "a hook" to attract adolescents, both in and out of school, and expose them to quality SRH information and services using varied formats.…”
Section: Discussioncontrasting
confidence: 68%
“…The high MH service uptake at first visit and the popularity of the MH service overall suggests that the MH service may have had a particularly strong influence on bringing young women to CHIEDZA. This finding is further supported by a qualitative study we conducted to explore the acceptability of the MH service within CHIEDZA [ 44 ]. Here, particularly during the COVID-19 pandemic, when markets were closed, less money was available in the household, and social activities and games within CHIEDZA were suspended, the MH service became the sole “ pull factor ” framing CHIEDZA as a “women’s service” and encouraging young women to visit CHIEDZA [ 44 , 47 ].…”
Section: Discussionsupporting
confidence: 55%
“…The reluctance to opt for and/or use the menstrual cup may be due to an unwillingness to try a novel menstrual product or unwillingness to use an insertable product that may affect their “virginity” [ 28 , 30 , 43 ]. These barriers persisted despite MH and menstrual cup sensitization and education provided through group talks, educational materials, and “menstrual cup champions” on site [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the study results showed high uptake of the MH service among young women as part of a multicomponent SRH service package. The provision of MH education, analgesics, and a choice of MH products through comprehensive MH interventions may serve as a pathway to increase female engagement with other important SRH services such as family planning and HIV testing (17,19,41,50).…”
Section: Discussionmentioning
confidence: 99%